SISTEM PENENTUAN DISKON PADA SWALAYAN BERBASIS JUMLAH PENJUALAN DAN STOK BARANG MENGGUNAKAN METODE FUZZY CONTROL - Sonalitha, Eltha (Department of Informatics Engineering, 2015)
Abstract-Competition supermarkets scattered everywhere with close proximity constraints have stock of goods in the supermarket is not immediately sold out even to reach the thresholds are exceeded. Sales management must be done to regulate the stock of goods in order to stock a lot of goods can be sold in advance. It is necessary to accelerate the inventory round. Monitoring and observation turnover should be done to determine the most salable goods and sought after by prospective customers with a high level of sales.In order to support the circulation of goods is required appropriate marketing strategies in the form of one of them by giving discounts on goods that are at risk of piling. The main target of this discounting is the amount of inventory that much and goods sales level slightly. The amount of stock that much should be given discounts in the hope that more rapid goods sold, thereby reducing the stock of goods that much. While the level of sales that little item must also be given a discount that much anyway so that goods are not up to the expiry date.This discount can not be separated determination of subjectivity manager self-service based on his experience as a sales management. Merging these two elements in determining the needs of this discount will rise to a complex calculation, to the researchers using fuzzy control methods to overcome them. The main objective of this research is to develop a system that can suppress the determination of prices of the losses suffered as a result of delays in circulation of goods. Research will implement determination system based discount rate of sales and inventory with fuzzy control in supermarkets. Keywords: Supermaket, Discounts, Fuzzy, Control